Polyvinyl alcohol composite film crosslinked by 1,2,3,4-butanetetracarboxylic acid, and preparation method and application thereof

CN122978622APending Publication Date: 2026-10-27HANGZHOU HIWETECH CHEM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611376707.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]针对聚乙烯醇耐水性差、阻燃性能不足及力学性能有限等问题,本发明提供了一种通过1,2,3,4-丁烷四羧酸交联的聚乙烯醇复合材料薄膜及其制备方法和应用

Benefits of technology

本发明构建聚乙烯醇分子链之间的稳定交联网络,有效降低材料的亲水性,显著提高聚乙烯醇复合薄膜的阻燃性、耐水性和力学性能,制备工艺简便,易于实现规模化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978622A_ABST
    Figure CN122978622A_ABST
Patent Text Reader

Abstract

The application discloses a polyvinyl alcohol composite film crosslinked by 1,2,3,4-butane tetracarboxylic acid and a preparation method and application thereof. The composite film takes polyvinyl alcohol as a matrix, introduces cellulose nanocrystals as a reinforcing agent, 1,2,3,4-butane tetracarboxylic acid as a crosslinking agent and phytic acid as a flame retardant, constructs a stable crosslinking network structure, and significantly improves the tensile strength, water resistance and flame retardant property of the polyvinyl alcohol composite film. The application uses renewable and green and environment-friendly raw materials, and combines a simple and efficient preparation process, realizes the synergistic improvement of the mechanical property and functional property of the polyvinyl alcohol composite film. The obtained composite film has excellent comprehensive performance, and has a wide application prospect in the fields of food packaging, agricultural films and other degradable green packaging materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polyvinyl alcohol composite films, specifically relating to a polyvinyl alcohol composite film crosslinked with 1,2,3,4-butanetetracarboxylic acid, its preparation method, and its application. Background Technology

[0002] Polyvinyl alcohol (PVA) is a highly representative water-soluble synthetic polymer, possessing both excellent physicochemical stability and complete biodegradability. Its molecular chain is rich in hydroxyl groups, endowing materials with outstanding film-forming and fiber-forming abilities. Films and fiber products prepared from PVA exhibit exceptional flexibility, extensibility, and molding performance, making them suitable for various molding processes such as blown film, spinning, casting, and coating. PVA-based materials have deeply penetrated diverse industries including textiles, fine chemicals, civil engineering materials, agricultural films, medical dressings, and food packaging, with their application scale continuously expanding. After disposal, PVA can gradually decompose under the action of microorganisms in soil and water, without forming persistent microplastic pollution, demonstrating enormous development potential in the fields of low-carbon environmental protection and plastic substitution.

[0003] Polyvinyl alcohol (PVA) molecules rely solely on weak hydrogen bonds for interaction, resulting in low chain slip resistance and a loose cross-linked network structure. This leads to low overall tensile strength and insufficient rigidity, making it prone to plastic deformation under stress and exhibiting poor elongation at break stability, thus failing to meet the requirements for high-strength structural bioplastics. Regarding water resistance, the presence of numerous hydrophilic hydroxyl groups gives PVA strong hydrophilicity, allowing it to rapidly absorb water, swell, soften, and even dissolve and disintegrate in humid or aquatic environments. Under prolonged humid and hot conditions, PVA materials exhibit volume expansion, interfacial delamination, and a significant decrease in mechanical properties. In terms of flame retardancy, PVA is a flammable polymer with a low limiting oxygen index, readily igniting and spreading rapidly upon contact with an open flame. Combustion is accompanied by melting and dripping, lacking self-extinguishing ability and producing large amounts of smoke, thus lacking basic fire-retardant properties. Summary of the Invention

[0004] To address the problems of poor water resistance, insufficient flame retardancy, and limited mechanical properties of polyvinyl alcohol (PVA), this invention provides a PVA composite film crosslinked with 1,2,3,4-butanetetracarboxylic acid (1,2,3,4-butanetetracarboxylic acid), its preparation method, and its applications. This composite film uses PVA as a matrix and incorporates cellulose nanocrystals, 1,2,3,4-butanetetracarboxylic acid, and phytic acid. Specifically, 1,2,3,4-butanetetracarboxylic acid crosslinks with the hydroxyl groups on the molecular chains of PVA and cellulose nanocrystals through esterification, constructing a stable covalent crosslinked network, enhancing interfacial bonding, and improving the structural integrity of the material. Phytic acid, as a phosphorus-containing flame retardant, effectively enhances the flame retardant properties of the composite film. Simultaneously, the esterification crosslinking reaction consumes some hydrophilic hydroxyl groups and forms a dense crosslinked network structure, reducing the material's adsorption of moisture, thereby significantly improving the tensile strength and water resistance of the composite film, achieving a synergistic improvement in mechanical properties, water resistance, and flame retardancy.

[0005] One of the technical solutions of the present invention is to provide a method for preparing a polyvinyl alcohol composite film, comprising the following steps: (1) Dissolve phytic acid in an aqueous dispersion of cellulose nanocrystals, with a mass ratio of phytic acid to cellulose nanocrystals of 1:3-3.3:1; (2) Dissolve 1,2,3,4-butanetetracarboxylic acid in the mixed liquid obtained in step (1); the mass ratio of 1,2,3,4-butanetetracarboxylic acid to cellulose nanocrystals is 9:1-0.9:1; 1,2,3,4-butanetetracarboxylic acid is used as a chemical crosslinking agent to connect PVA and cellulose through covalent bonds. Compared with hydrogen bonds, covalent bonds have higher bonding strength and better stability. 1,2,3,4-butanetetracarboxylic acid does not simply pull a "rope" between PVA and cellulose, but uses four active sites to simultaneously grab multiple PVA segments and hydroxyl groups on the surface of cellulose microfibrils to form a three-dimensional anchoring structure. This multi-arm anchoring greatly restricts the slippage of molecular chains at the interface.

[0006] (3) Add the mixed liquid obtained in step (2) to the polyvinyl alcohol aqueous solution and mix evenly to obtain a mixed liquid, and then remove the air in the mixed liquid; the mass ratio of polyvinyl alcohol to phytic acid is 97:1-9.7:1; (4) Pour the mixed liquid obtained in step (3) into a mold, heat it in an oven at 60°C for 7 hours, and then heat it in an oven at 150°C for 15 minutes to undergo an esterification reaction to obtain a polyvinyl alcohol composite film.

[0007] Furthermore, the concentration of phytic acid in the aqueous dispersion of cellulose nanocrystals is 0.2-2.4 wt%.

[0008] Furthermore, the concentration of the cellulose nanocrystal aqueous dispersion is 0.7-0.74 wt%.

[0009] Furthermore, the concentration of the polyvinyl alcohol aqueous solution is 6.5 wt%.

[0010] Furthermore, in step (3), the mixing method is ultrasonic treatment for 20 minutes.

[0011] Furthermore, the method for removing air from the mixed liquid is to evacuate for 90 minutes.

[0012] Furthermore, the method for preparing the polyvinyl alcohol aqueous solution is as follows: after dispersing polyvinyl alcohol in deionized water, stir at 90°C for 1 hour.

[0013] The second technical solution of the present invention is to provide a polyvinyl alcohol composite film prepared by the above method.

[0014] The third technical solution of this invention is to provide applications for the aforementioned polyvinyl alcohol composite film. These applications are in the fields of food packaging or agricultural films.

[0015] The advantages of this invention are: This invention constructs a stable cross-linked network between polyvinyl alcohol molecular chains, effectively reducing the hydrophilicity of the material and significantly improving the flame retardancy, water resistance, and mechanical properties of polyvinyl alcohol composite films. The preparation process is simple and easy to scale up.

[0016] The polyvinyl alcohol composite film prepared by this invention has excellent flame retardancy, high strength and water resistance, and can be widely used in food packaging, agricultural film and other green packaging materials, with broad application prospects and promotion value. Attached Figure Description

[0017] Figure 1 This is the stress-strain curve of pure polyvinyl alcohol in Comparative Example 1.

[0018] Figure 2 This is the stress-strain curve of the polyvinyl alcohol composite film in Example 1.

[0019] Figure 3 This refers to the expansion degree of the polyvinyl alcohol composite film in this invention.

[0020] Figure 4 It is the limiting oxygen index of the polyvinyl alcohol composite film in this invention. Detailed Implementation

[0021] The following examples are provided to further illustrate the present invention and are intended to explain the invention, not to limit its scope. Unless otherwise specified, all figures are expressed in parts by weight and weight percentages.

[0022] Unless otherwise specified, the raw materials used in this invention are all conventional commercially available products; unless otherwise specified, the methods used in this invention are all conventional methods in the field.

[0023] The embodiments of the present invention will be further described below with reference to several examples.

[0024] It should be understood that the described embodiments are merely some, not all, of the embodiments in this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application without inventive effort are within the scope of protection of this application.

[0025] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0026] Example 1 (1) Dissolve 4.85g of polyvinyl alcohol in 70ml of deionized water and stir in an oil bath at 90℃ for 1h to obtain a 6.5wt% polyvinyl alcohol aqueous solution. (2) Disperse 0.15g of cellulose nanocrystals in 20ml of deionized water and stir at room temperature for 30min to obtain a uniformly dispersed 0.74 wt% cellulose nanocrystal suspension; (3) Add 0.05g of phytic acid to the cellulose nanocrystal suspension and stir for 30min; (3) Add 0.45g of 1,2,3,4-butanetetracarboxylic acid to the cellulose nanocrystal suspension and stir for 30min; (4) Add the cellulose nanocrystal suspension to the polyvinyl alcohol solution and stir for 1 hour; (5) The mixed liquid is ultrasonically vibrated in an ultrasonic cleaner for 20 minutes, and then vacuumed to remove bubbles for 90 minutes; (6) Pour the defoamed liquid into a mold, dry it in an oven at 60°C for 7 hours, and then heat it in an oven at 150°C for 15 minutes to obtain a polyvinyl alcohol composite film; Figure 1 and Figure 2As shown, the tensile strength of the polyvinyl alcohol composite film in Example 1 exceeds 60 MPa, which is higher than that of the pure polyvinyl alcohol film (Comparative Example 1), and the elastic modulus is also significantly improved. This performance improvement comes from two aspects: firstly, under the action of 1,2,3,4-butanetetracarboxylic acid, the reinforcing agent cellulose nanocrystals can be uniformly dispersed in polyvinyl alcohol; secondly, 1,2,3,4-butanetetracarboxylic acid, polyvinyl alcohol, and cellulose nanocrystals form a tight three-dimensional structure through a cross-linking reaction, which can restrict the sliding and relative movement of molecular chains and effectively transfer stress from the matrix to the cellulose nanocrystals.

[0027] Example 2 (1) Dissolve 4.85g of polyvinyl alcohol in 70ml of deionized water and stir in an oil bath at 90℃ for 1h to obtain a 6.5wt% polyvinyl alcohol aqueous solution. 0.15 g of cellulose nanocrystals were dispersed in 20 ml of deionized water and stirred at room temperature for 30 min to obtain a uniformly dispersed 0.74 wt% cellulose nanocrystal suspension. (2) Add 0.1g of phytic acid to the cellulose nanocrystal suspension and stir for 30min; (3) Add 0.45g of 1,2,3,4-butanetetracarboxylic acid to the cellulose nanocrystal suspension and stir for 30min; (4) Add the cellulose nanocrystal suspension to the polyvinyl alcohol solution and stir for 1 hour; (5) The mixed liquid is ultrasonically vibrated in an ultrasonic cleaner for 20 minutes, and then vacuumed to remove bubbles for 90 minutes; (6) Pour the defoamed liquid into a mold, dry it in an oven at 60°C for 7 hours, and then heat it in an oven at 150°C for 15 minutes to obtain a polyvinyl alcohol composite film.

[0028] Example 3 (1) Dissolve 4.85g of polyvinyl alcohol in 70ml of deionized water and stir in an oil bath at 90℃ for 1h to obtain a 6.5wt% polyvinyl alcohol aqueous solution. 0.15 g of cellulose nanocrystals were dispersed in 20 ml of deionized water and stirred at room temperature for 30 min to obtain a uniformly dispersed 0.74 wt% cellulose nanocrystal suspension. (2) Add 0.25g of phytic acid to the cellulose nanocrystal suspension and stir for 30min; (3) Add 0.45g of 1,2,3,4-butanetetracarboxylic acid to the cellulose nanocrystal suspension and stir for 30min; (4) Add the cellulose nanocrystal suspension to the polyvinyl alcohol solution and stir for 1 hour; (5) The mixed liquid is ultrasonically vibrated in an ultrasonic cleaner for 20 minutes, and then vacuumed to remove bubbles for 90 minutes; (6) Pour the defoamed liquid into a mold, dry it in an oven at 60°C for 7 hours, and then heat it in an oven at 150°C for 15 minutes to obtain a polyvinyl alcohol composite film.

[0029] Example 4 (1) Dissolve 4.85g of polyvinyl alcohol in 70ml of deionized water and stir in an oil bath at 90℃ for 1h to obtain a 6.5wt% polyvinyl alcohol aqueous solution. 0.15 g of cellulose nanocrystals were dispersed in 20 ml of deionized water and stirred at room temperature for 30 min to obtain a uniformly dispersed 0.74 wt% cellulose nanocrystal suspension. (2) Add 0.5g of phytic acid to the cellulose nanocrystal suspension and stir for 30min; (3) Add 0.45g of 1,2,3,4-butanetetracarboxylic acid to the cellulose nanocrystal suspension and stir for 30min; (4) Add the cellulose nanocrystal suspension to the polyvinyl alcohol solution and stir for 1 hour; (5) The mixed liquid is ultrasonically vibrated in an ultrasonic cleaner for 20 minutes, and then vacuumed to remove bubbles for 90 minutes; (6) Pour the defoamed liquid into a mold, dry it in an oven at 60°C for 7 hours, and then heat it in an oven at 150°C for 15 minutes to obtain a polyvinyl alcohol composite film.

[0030] Comparative Example 1 (1) Dissolve 4.85g of polyvinyl alcohol in 70ml of deionized water and stir in an oil bath at 90℃ for 1h to obtain a 6.5wt% polyvinyl alcohol aqueous solution. (2) The polyvinyl alcohol solution was ultrasonically vibrated in an ultrasonic cleaner for 20 minutes, and then vacuumed to remove bubbles for 90 minutes; (3) Pour the defoamed solution into a mold and place it in an oven at 60°C for 7 hours to obtain a pure polyvinyl alcohol film.

[0031] Comparative Example 2 (1) Dissolve 4.85g of polyvinyl alcohol in 70ml of deionized water and stir in an oil bath at 90℃ for 1h to obtain a 6.5wt% polyvinyl alcohol aqueous solution. (2) Disperse 0.15g of cellulose nanocrystals in 20ml of deionized water and stir at room temperature for 30min to obtain a uniformly dispersed 0.74 wt% cellulose nanocrystal suspension; (3) Add the cellulose nanocrystal suspension to the polyvinyl alcohol solution and stir for 1 hour; (4) The mixed liquid is ultrasonically vibrated in an ultrasonic cleaner for 20 minutes, and then vacuum defoamed for 90 minutes; (5) Pour the defoamed liquid into a mold and place it in an oven at 60°C for 7 hours to obtain a polyvinyl alcohol / cellulose nanocrystal film.

[0032] Comparative Example 3 (1) Dissolve 4.85g of polyvinyl alcohol in 70ml of deionized water and stir in an oil bath at 90℃ for 1h to obtain a 6.5wt% polyvinyl alcohol aqueous solution. (2) Disperse 0.15g of cellulose nanocrystals in 20ml of deionized water and stir at room temperature for 30min to obtain a uniformly dispersed 0.74 wt% cellulose nanocrystal suspension; (3) Add 0.45g of 1,2,3,4-butanetetracarboxylic acid to the cellulose nanocrystal suspension and stir for 30min; (4) Add the cellulose nanocrystal suspension to the polyvinyl alcohol solution and stir for 1 hour; (5) The mixed liquid is ultrasonically vibrated in an ultrasonic cleaner for 20 minutes, and then vacuumed to remove bubbles for 90 minutes; (6) Pour the defoamed liquid into a mold, dry it in an oven at 60°C for 7 hours, and then heat it in an oven at 150°C for 15 minutes to obtain a polyvinyl alcohol composite film.

[0033] Comparative Example 4 (1) Dissolve 4.85g of polyvinyl alcohol in 70ml of deionized water and stir in an oil bath at 90℃ for 1h to obtain a 6.5wt% polyvinyl alcohol aqueous solution. 0.15 g of cellulose nanocrystals were dispersed in 20 ml of deionized water and stirred at room temperature for 30 min to obtain a uniformly dispersed 0.74 wt% cellulose nanocrystal suspension. (2) Add 0.01g of phytic acid to the cellulose nanocrystal suspension and stir for 30min; (3) Add 0.45g of 1,2,3,4-butanetetracarboxylic acid to the cellulose nanocrystal suspension and stir for 30min; (4) Add the cellulose nanocrystal suspension to the polyvinyl alcohol solution and stir for 1 hour; (5) The mixed liquid is ultrasonically vibrated in an ultrasonic cleaner for 20 minutes, and then vacuumed to remove bubbles for 90 minutes; (6) Pour the defoamed liquid into a mold, dry it in an oven at 60°C for 7 hours, and then heat it in an oven at 150°C for 15 minutes to obtain a polyvinyl alcohol composite film.

[0034] like Figure 3As shown, Comparative Examples 1 and 2 completely dissolved after immersion in water for 24 hours, while Examples 1, 2, 3, and 4 remained intact after immersion for 24 hours, only experiencing some degree of swelling, with the swelling degree being less than 260%. This is because during the cross-linking reaction, 1,2,3,4-butanetetracarboxylic acid undergoes esterification with the hydroxyl groups on the polyvinyl alcohol and cellulose nanocrystal molecular chains, forming a stable three-dimensional covalent cross-linked network. Simultaneously, some hydrophilic hydroxyl groups are consumed, reducing the material's affinity for water molecules. The cross-linked network effectively restricts the movement and swelling of the polymer molecular chains, allowing the composite film to maintain its intact structure in water without dissolving.

[0035] like Figure 4 As shown, the limiting oxygen index (LOI) of Comparative Examples 1 and 4 was below 19%, while the LIO of Examples 1, 2, 3, and 4 was above 19%, with Example 4 reaching an LIO of 24.9%, indicating that the composite film has excellent flame-retardant properties. Examples 1-4 and Comparative Examples 1 and 4 show that when the mass ratio of 1,2,3,4-butanetetracarboxylic acid to phytic acid is controlled between 9:1 and 0.9:1, the resulting polyvinyl alcohol composite film has a high LIO and good flame-retardant properties. When the mass ratio is higher than 9:1, the LIO and flame-retardant properties of the resulting film decrease significantly. This indicates that the ratio of 1,2,3,4-butanetetracarboxylic acid to phytic acid has a significant impact on the flame-retardant properties of the composite material. The reason for its flame retardancy is that phytic acid molecules are rich in phosphate groups, which can decompose upon heating to generate dehydrated acidic substances such as metaphosphoric acid and polyphosphoric acid. These acidic components can catalyze the dehydration and carbonization reaction of the polyvinyl alcohol molecular chains, rapidly forming a continuous, dense, and stable carbon-rich layer on the material surface. This carbon layer can effectively isolate oxygen from entering the material, hinder heat transfer, and suppress the release of combustible volatile products generated by the pyrolysis of polyvinyl alcohol, thereby slowing down the combustion chain reaction, increasing the oxygen concentration required for the material to maintain combustion, and ultimately significantly improving the limiting oxygen index and flame retardant properties of the polyvinyl alcohol composite film.

[0036] The above embodiments detail the structure, features, and effects of the present invention. The above descriptions are merely preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or equivalent embodiments modified to have equivalent variations, shall still fall within the scope of protection of the present invention if they do not exceed the scope covered by the specification.

Claims

1. A polyvinyl alcohol composite film crosslinked with 1,2,3,4-butanetetracarboxylic acid, characterized in that, It includes the following steps: (1) Dissolve phytic acid in an aqueous dispersion of cellulose nanocrystals, with a mass ratio of phytic acid to cellulose nanocrystals of 1:3-3.3:1; (2) Dissolve 1,2,3,4-butanetetracarboxylic acid in the mixed liquid obtained in step (1); the mass ratio of 1,2,3,4-butanetetracarboxylic acid to phytic acid is 9:1-0.9:1; (3) Add the mixed liquid obtained in step (2) to the polyvinyl alcohol aqueous solution and mix evenly to obtain a mixed liquid, and then remove the air in the mixed liquid; the mass ratio of polyvinyl alcohol to phytic acid is 97:1-9.7:1; (4) Pour the mixed liquid obtained in step (3) into a mold, heat it in an oven at 60°C for 7 hours, and then heat it in an oven at 150°C for 15 minutes to undergo an esterification reaction to obtain a polyvinyl alcohol composite film.

2. The method according to claim 1, characterized in that, The concentration of phytic acid in the aqueous dispersion of cellulose nanocrystals is 0.2-2.4 wt%.

3. The method according to claim 1, characterized in that, The concentration of the cellulose nanocrystal aqueous dispersion is 0.7-0.74 wt%.

4. The method according to claim 1, characterized in that, The concentration of the polyvinyl alcohol aqueous solution is 6.5 wt%.

5. The method according to claim 1, characterized in that, The mixing method in step (3) is ultrasonic treatment for 20 minutes.

6. The method according to claim 1, characterized in that, The method for removing air from the mixed liquid is to evacuate for 90 minutes.

7. The method according to claim 1, characterized in that, The method for preparing the polyvinyl alcohol aqueous solution is as follows: after dispersing polyvinyl alcohol in deionized water, stir at 90°C for 1 hour.

8. A polyvinyl alcohol composite film prepared by the method according to any one of claims 1-7.

9. The application of a polyvinyl alcohol composite film as described in claim 8.

10. The application according to claim 9, characterized in that, The applications are in the fields of food packaging or agricultural film.